Reversible Inter- and Intra-Microgel Cross-Linking using Disulfides - Gaulding, Jeffrey C. (2012)
Thermoresponsive hydrogel nanoparticles composed of poly(N-isopropylmethacrylamide) (pNIPMAm) and the disulfide-based cross-linker N,N’-bis(acryloyl)cystamine (BAC) have been prepared using a redox-initiated, aqueous precipitation polymerization approach, leading to improved stability of the disulfide bond compared to traditional thermally-initiated methods. The resultant particles demonstrate complete erosion in response to reducing conditions or thiol competition. This stands in contrast to the behavior of thermally-initiated particles, which retain a cross-linked network following disulfide cleavage due to uncontrolled chain-branching and self-cross-linking side reactions. The synthetic strategy has also been combined with the non-degradable cross-linker N,N-methylenebisacrylamide (BIS) to generate “co-cross-linked” pNIPMAm-BAC-BIS microgels. These particles are redox-responsive, swell upon BAC cross-link scission and present reactive thiols. This pendant thiol functionality was demonstrated to be useful for conjugation of thiol-reactive probes and in reversible network formation by assembling particles cross-linked by disulfide linkages.